2021
DOI: 10.1017/s1049023x2000151x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19 IgG Antibodies in a Cohort of Municipal First Responders

Abstract: Background: Although first responders (FRs) represent a high-risk group for exposure, little information is available regarding their risk of coronavirus disease 2019 (COVID-19) infection. The purpose of the current study was to determine the serological prevalence of past COVID-19 infection in a cohort of municipal law enforcement (LE) and firefighters (FFs). Methods: Descriptive analysis of a de-identified data reporting Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“… 12 Studies of emergency responders in Arizona and Minnesota conducted from late April to May 2020 found seroprevalences of 1.5% and 1.2% respectively. 13 , 14 In April 2020, during a local outbreak in South Florida, seroprevalence was found to be 8.9% in emergency responders. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Studies of emergency responders in Arizona and Minnesota conducted from late April to May 2020 found seroprevalences of 1.5% and 1.2% respectively. 13 , 14 In April 2020, during a local outbreak in South Florida, seroprevalence was found to be 8.9% in emergency responders. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Serologic surveys of first responders have shown variable results with some showing rates similar to the general population and others showing higher rates (see Table 1). [1][2][3][4][5][6][7] Some of this variability may relate to differences in access to personal protective equipment (PPE) and infection control policies. [8] Because high-risk groups such as older individuals and individuals with significant comorbidities may be underrepresented among first responders, the proportion of infections which are asymptomatic in this group may be higher.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Although it has been demonstrated that healthcare workers with high levels of patient contact experience greater odds of seropositivity than the general population or other public service employees, [4,7] seroprevalence among first responders or firefighters do not appear to significantly deviate from community estimates. [1,2,6] In this study we conducted a serologic survey to estimate the prevalence of SARS-CoV-2 antibodies among firefighters in the Los Angeles Fire Department (LAFD) and tested for associations between seroprevalence and individual characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…On the lower end, seroprevalence estimates ranged from 1.1% and 1.5% in Rochester (May) and Arizona (April/May), respectively. [1,2] In May/June seroprevalence was 5.4% in Cleveland 6.9% in Detroit. [3,4] In a single fire department located at the epicenter of an outbreak in South Florida, seroprevalence was 8.9% in April.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation